Exploring the Delivery of Perinatal Care Services for Individuals Incarcerated in Ontario, Canada: A Case Study - Bancroft, Xaand (Université d'Ottawa / University of Ottawa, 2026)
Background: Incarcerated pregnant individuals in Ontario, Canada, face significant barriers to equitable, timely, and appropriate perinatal care, which may result in health disparities and adverse outcomes for both parents and newborns compared to the general population. Understanding these disparities requires a multi-level analysis of the lived experiences of individuals pregnant while incarcerated, the professional experiences of providers, and the institutional policies governing care. Guided by a Reproductive Justice framework, this thesis identifies systemic challenges within the provincial carceral system impacting perinatal care equity. Purpose: The purpose of this thesis was to examine how perinatal care is delivered to individuals incarcerated in Ontario, Canada, and to identify system-level factors influencing access to and continuity of care. Methods: This research employed an explanatory case study approach, utilizing the explanation-building analytical technique to stipulate causal links and explain the mechanisms underlying perinatal care delivery. The study utilized semi-structured interviews to capture the lived and professional experiences of patients and providers. These qualitative data informed a structural analysis (MICMAC) and causal loop diagramming to model system dynamics and identify key leverage points. Separately, Institutional Grammar 2.0 was used to conduct a systematic analysis of federal and provincial carceral perinatal policies. All findings were triangulated and analyzed through a Reproductive Justice lens. Results: Institutional Grammar 2.0 analysis revealed that non-medical correctional actors hold authority in over half of the policy statements - significantly more than healthcare providers or incarcerated individuals. Furthermore, policy provisions fail to support bodily autonomy, and key provincial legislation supporting reproductive rights is not entered into force. The integrated structural and causal-loop analysis identified Availability of providers, Carceral staff autonomy, and Advocacy as key leverage points within the perinatal carceral setting. These findings demonstrate how prioritizing carceral authority over health and social services creates systemic barriers to equitable perinatal care and patient autonomy. Conclusion: This thesis reveals perinatal care in Ontario to be structurally fragmented, operating under conflicting mandates in which carceral security frequently takes precedence over patient health. The findings demonstrate a fundamental incongruity between the current carceral state and reproductive rights, as institutional norms and power asymmetries consistently undermine bodily autonomy. While immediate interventions may mitigate these conditions, they do not resolve the system's inherent structural flaws. Therefore, achieving reproductive justice requires a shift away from punitive confinement toward supportive, community-based models and the abolition of incarceration during the perinatal period.
Keywords: Maternal health; Perinatal care; Incarceration; Reproductive justice; Qualitative analysis; Policy analysis; Structural Analysis; Systems thinking; Causal loop diagram; Health systems; Matrice d'Impacts Croisés Multiplication Appliquée à un Classement (MICMAC) analysis